An exploratory study on the effectiveness of the recruitment and selection process of Square Toiletries Limited - Abrar, Khandker Nabil (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.